Risks and Threats Posed to a Company’s Economic Security - Valeryevich Bank, Sergey; Dmitriyevich Sekerin, Vladimir; Evgenievna Gorokhova, Anna; Ivanovich Nikolaykin, Nikolay; Gennadievich Shcherbakov, Anton (International Journal of Engineering and Technology, 2018)
This paper examines some of the major types of risks and threats that may be posed to the economic security of national enterprises. Its purpose is to terminologically fine-tune the categories â€˜threatsâ€™ and â€˜riskâ€™, analyze and classify risks from the standpoint of the multicriteria approach, as well as fine-tune existing methods for assessing risks faced by a firmâ€™s economic security system. Based on the findings from their analysis of relevant materials, the authors have formulated the following conclusions:â€¢an event that does not yield itself to assessment from the standpoint of quantitative and qualitative parameters is regarded as a threat. In this context, it becomes virtually impossible to come up with efficient preventive activities, as it is problematic to conduct quantitative assessments of this kind of event. Reducing the extent of a threat requires identifying and classifying relevant risks;â€¢a modern enterprise is a backbone element in the national economy. Managing risks and threats posed to economic security at the microlevel is a part of the national strategy for social/economic development in the Russian Federation. This is why threats that emerge at the level of interaction among business entities are strategic risks;â€¢assessing risk implies not only identifying the intensity of negative impact factors but constructing its specific forms as well. Assessment procedures are based on detecting negative impact factors, establishing the degree of their impact on a firmâ€™s economic security system, and forecasting the potential reactions of the firmâ€™s subsystems. The most frequently used assessment methods are expert and mathematical methods.Â Â